In search of an enabling pedagogy for HIV and AIDS Education in initial teacher education - Wilmot, Di; Wood, Lesley (South African Journal of Higher Education, 2016)
This article addresses the issue of teacher knowledge in a developing world context of HIV and AIDS. More specifically, it responds to the need for practical ‘how to’ examples of HIV and AIDS education by describing the pedagogical strategies employed in an initial teacher education programme at a South African university. An overview of the theoretical constructs underpinning the module development and implementation is given, followed by a detailed description and justification of the qualitative research design and methodology employed to answer the research question: “How can HIV and AIDS education be effectively integrated into an initial teacher education programme?” The findings of the study provide evidence of how the intervention’s active learning approach facilitated the teachers’ acquisition of the knowledge, skills and attitudes needed for effective HIV prevention education. The article may offer other teacher educators some guidelines on how to integrate HIV and AIDS education into their own programmes.